Heart Rate of Reticulated Pythons (Malayopython reticulatus) from Bali based on Its Body Length (DETAK JANTUNG ULAR SANCA BATIK (Malayopython reticulatus) BERDASARKAN PANJANG TUBUH DI BALI) - Purbantoro, Steven Dwi; Govendan, Puveanthan Nagappan; Erawan, I Gusti Made Krisna; Christiani, Zefanya; Erika, Erika; Rumbay, Yedija Putra Kusuma Wardana; Raharjo, Slamet (Jurnal Veteriner, 2019)
This study was aimed to determine the correlation between heart rate and body length of reticulated python (Malayopython reticulatus) from the island of Bali. The study offers data of the M. reticulatus heart rate value to exotic animal veterinary practitioner. Fifteen clinically healthy snakes, consists of 9 females and 6 males were used in this study. Heart rate was measured twice a day during day and night using a fetal Doppler (BF-500 eBestman®, China) and body length using a measurement tape. Heart rate was analyzed with independent t-test to time collection and correlation to body length. Results show that heart rate mean value at day and night of the M. reticulatus from the island of Bali was each 65.68±14.093 bpm and 64.53±13.637 bpm. Heart rate value of wild-caught snakes is higher (67.90±15.290 bpm) than captivebred snakes (60.92±10.039 bpm). Total length (TL), snout-vent length (SVL), and snout-heart length (SHL) mean value of M. reticulatus from the island of Bali was each 168.6±90.67 cm, 149.53±82.77 cm, and 38.7±19.28 cm. Correlation between heart rate and total length has higher R-value (R = 0.802), and followed by snout-heart length (R = 0.800) and snout-vent length (R = 0.792). Statistically, it could be concluded that heart rate during day and night time shows no significant difference, heart rate value based on how it is kept is significantly different, and heart rate was negatively correlated to body length.